Edukasi Stop Bullying Pada Siswa Dan Wali Murid Di Desa Curahsawo - Jannah, Faridahtul; Ilmia, Ilmia; Suharwati, Zulkha; Oktaviaji, Firda; Ludfi Arya Wardana (Journal Of Human And Education (JAHE), 2024)
Cases of bullying that occur in the community, especially schools, often become hot topics of discussion. This is due to a lack of insight and education about the impact and prevention of bullying. If this bullying case is not handled immediately from an early age, it will continue and have negative impacts in the future. Therefore, KKN students from Panca Marga University Probolinggo who were placed in Curahsawo Village raised this problem as a work program in an effort to prevent bullying cases occurring among the community, especially in elementary schools. The efforts made by students are to provide education through outreach to several students and their parents. The method used in implementing PKM activities is socialization using counseling techniques in the form of lectures or presenting material in the form of theory and videos related to the theme we are taking as well as questions and answers. The results achieved from implementing this work program are that by providing socialization regarding bullying, the community and students can understand more about the impact of bullying behavior and how to prevent it as well as existing laws. Parents can also introduce and teach children about the types of bullying and the dangers of bullying. Students can also learn more deeply that bullying is a bad act and is very detrimental to other people, even themselves